Do family ties with those left behind intensify or weaken migrants' assimilation? - Oded Stark; Agnieszka Dorn (University of Bonn, Center for Development Research (ZEF), 2012)
Strong ties with the home country and with the host country can coexist. An altruistic migrant who sends remittances to his family back home assimilates more the more altruistic he is, and also more than a non-remitting migrant.
Keywords: D01; D13; D64; F22; F24; 330; Assimilation of migrants; Acculturation identity; Links with the home country; Altruism; Remittances; Migranten; Soziale Integration; Rücküberweisung (Migranten); Familie